2008
DOI: 10.1038/sj.jid.5701107
|View full text |Cite
|
Sign up to set email alerts
|

Human Skin Keloid Fibroblasts Display Bioenergetics of Cancer Cells

Abstract: Cultured human skin keloid fibroblasts (KFs) showed bioenergetics similar to cancer cells in generating ATP mainly from glycolysis as demonstrated by increased lactate production. Activities of hexokinase, glyceraldehyde-3-phosphate dehydrogenase, and lactate dehydrogenase were also significantly higher compared with normal fibroblasts (NFs). Inhibitors of glycolysis decreased the rate of ATP biosynthesis more significantly in KFs suggesting their reliance on glycolysis. In contrast, ATP generation in NFs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 49 publications
(49 reference statements)
4
95
1
Order By: Relevance
“…36,37 In accordance with this notion, keloid fibroblasts (derived from non-tumorous "scarred skin") show many of the same characteristics as Cav-1 deficient tumor stroma, with activation of HIF1-a and NFκB, as well as a shift towards aerobic glycolysis. 27,38,39 Thus, there may be a mechanistic connection between loss of Cav-1 as a driver of tissue fibrosis, tumor progression and metastasis. 40 Consistent with this notion, a fibrotic focus in breast cancers is thought to be a surrogate marker for hypoxia.…”
Section: Discussionmentioning
confidence: 98%
“…36,37 In accordance with this notion, keloid fibroblasts (derived from non-tumorous "scarred skin") show many of the same characteristics as Cav-1 deficient tumor stroma, with activation of HIF1-a and NFκB, as well as a shift towards aerobic glycolysis. 27,38,39 Thus, there may be a mechanistic connection between loss of Cav-1 as a driver of tissue fibrosis, tumor progression and metastasis. 40 Consistent with this notion, a fibrotic focus in breast cancers is thought to be a surrogate marker for hypoxia.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, A549 and H1299 cells shifted their metabolism to OXPHOS in response to CAF stimulation. Although the occurrence of the Warburg effect in cancer cells was first proposed by Otto H. Warburg in the early 1920s [8], in 2008, Vincent et al demonstrated that skin myofibroblasts experience aerobic glycolysis exactly like cancer cells [48]. Furthermore, Lisanti et al revealed that caveolin-1-deficient CAFs show the upregulation of both myofibroblast markers and glycolytic enzymes under normoxic conditions and this was associated with the recurrence, metastasis, and poor outcome of human breast cancer [9].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in 2008, Vincent et al demonstrated that human skin keloid fibroblasts display similar bioenergetic changes as cancer cells in generating ATP mainly from glycolysis. The hypoxic microenvironment is a common fact in solid tumors and keloids, which may be the explanation for this thermodynamic phenomenon [4]. In line with these findings, Pavlides and col suggested, in 2009, a novel hypothesis for understanding the Warburg effect in tumors [5]: they proposed that epithelial cancer cells induce the Warburg effect in neighboring stromal fibroblasts.…”
Section: Introductionmentioning
confidence: 93%